2020
DOI: 10.1021/acssuschemeng.0c04372
|View full text |Cite
|
Sign up to set email alerts
|

Red Phosphorus/Carbon Nitride van der Waals Heterostructure for Photocatalytic Pure Water Splitting under Wide-Spectrum Light Irradiation

Abstract: Developing active photocatalysts using wide-spectrum light is crucial to promote the application of photocatalytic water splitting. Elemental red phosphorus (RP) has attracted much attention as a potential nonmetal photocatalyst owing to its low cost, earth abundance, and narrow bandgap. Herein, RP nanosheets were synthesized and tightly combined with carbon nitride (CN) framework nanosheets to form RP/CN van der Waals (vdW) heterostructure. CN nanosheets could act as a substrate to generate RP nanosheets thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…Red phosphorus (RP)/carbon nitride (CN) vdWh were synthesized by Wang et al, and the CN nanosheets can be used as substrates to produce RP nanosheets through a "confinement effect" (see Figure 9e). [97] The composite photocatalyst could decompose pure water by incident light with a wavelength greater than 620 nm, and its hydrogen evolution rate was 367.0 µmol h −1 g −1 in the full arc diagram and 239.8 µmol h −1 g −1 for visible light. The improved of photocatalytic performance was attributed to the broad-spectrum absorption and tight electron interactions in a RP/CN vdWh, which accelerated CT. Table 1 summarizes the main experimental results of vdWhs for hydrogen production in recent years, including heterojunction structure, preparation method, light source, hydrogen production efficiency, and the corresponding years for comparison.…”
Section: Photocatalysismentioning
confidence: 95%
See 4 more Smart Citations
“…Red phosphorus (RP)/carbon nitride (CN) vdWh were synthesized by Wang et al, and the CN nanosheets can be used as substrates to produce RP nanosheets through a "confinement effect" (see Figure 9e). [97] The composite photocatalyst could decompose pure water by incident light with a wavelength greater than 620 nm, and its hydrogen evolution rate was 367.0 µmol h −1 g −1 in the full arc diagram and 239.8 µmol h −1 g −1 for visible light. The improved of photocatalytic performance was attributed to the broad-spectrum absorption and tight electron interactions in a RP/CN vdWh, which accelerated CT. Table 1 summarizes the main experimental results of vdWhs for hydrogen production in recent years, including heterojunction structure, preparation method, light source, hydrogen production efficiency, and the corresponding years for comparison.…”
Section: Photocatalysismentioning
confidence: 95%
“…The improved of photocatalytic performance was attributed to the broad-spectrum absorption and tight electron interactions in a RP/CN vdWh, which accelerated CT. Table 1 summarizes the main experimental results of vdWhs for hydrogen production in recent years, including heterojunction structure, preparation method, light source, hydrogen production efficiency, and the corresponding years for comparison. [75,94,[96][97][98][99][100][101] In terms of photocatalytic CO 2 reduction, Li et al prepared atom thick CN/Bi 9 O 7.5 S 6 (BOS) vdWh for CO 2 photoreduction (see Figure 10a). [102] Experiments and theoretical calculations showed that CO* adsorbed stronger than CN, and could be hydrogenated before desorption, which explained why the main products of photocatalytic CO 2 reduction on BOS were CH 4 and CH 3 OH.…”
Section: Photocatalysismentioning
confidence: 99%
See 3 more Smart Citations